2018
DOI: 10.1002/elps.201700286
|View full text |Cite
|
Sign up to set email alerts
|

Electric double layer electrostatics of lipid‐bilayer‐encapsulated nanoparticles: Toward a better understanding of protocell electrostatics

Abstract: Lipid-bilayer-encapsulated nanoparticles (LBLENPs) or NP-supported LBL systems, such as protocells (which are lipid bilayer encapsulated mesoporous silica nanoparticles or MSNPs) have received extensive attention for applications like targeted drug and gene deliveries, multimodal diagnostics, characterization of membrane-geometry sensitive molecules, etc. Very often electrostatic-mediated interactions have been hypothesized to play key roles in the functioning of these LBLENPs. Despite that, very little has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The multilayer thin films composed of functional organic molecules, enzymes, and lectins also respond to substrates, such as pH [ 21 , 22 ], electrical potential [ 23 ], glucose, lactate, and hydrogen peroxide [ 24 , 25 , 26 ]. Such functional multilayer thin films could be useful for separation and purification [ 27 , 28 ], sensors [ 29 , 30 ], and drug delivery systems [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multilayer thin films composed of functional organic molecules, enzymes, and lectins also respond to substrates, such as pH [ 21 , 22 ], electrical potential [ 23 ], glucose, lactate, and hydrogen peroxide [ 24 , 25 , 26 ]. Such functional multilayer thin films could be useful for separation and purification [ 27 , 28 ], sensors [ 29 , 30 ], and drug delivery systems [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such choice of interfacial charge is reasonable for the cellmembrane-coated NPs. 27 We observe that the interfacial potential y 0 and the electrophoretic mobility μ E /μ 0 increases with the increase in concentration of additional mobile ions across the liquid layer and its effect is prominent for low electrolyte concentration. On the other hand, for electrolytes with high concentration, the shielding effect has a prominent role to screen the interfacial surface charge, which further reduces the effective electric potential along the surface of the liquid layer.…”
Section: Resultsmentioning
confidence: 72%
“…The interfacial charge is varied, changing the parameter S from 500 Å 2 to 50 000 Å 2 , which results in the range for interfacial charge σ from 0.032 C/m 2 to 0.00032 C/m 2 . Such choice of interfacial charge is reasonable for the cell-membrane-coated NPs . We observe that the interfacial potential y 0 and the electrophoretic mobility μ E /μ 0 increases with the increase in concentration of additional mobile ions across the liquid layer and its effect is prominent for low electrolyte concentration.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…However, those investigations have addressed mainly charged particles without any polymer coating layer [17]. Nowadays, polyelectrolyte grafted nanochannels (also called soft nanochannels) were widely studied for the development of nanofluidics achieving diode-like behavior, energy conversion and the detection of biomolecules [18,19,20,21,22,23], while polyelectrolyte adsorbed particles (also called soft particles) were employed for controlling colloidal stability and drug delivery [24,25,26,27,28]. All Email address: js.sin@ryongnamsan.edu.kp (Jun-Sik Sin) the studies confirmed that compared to conventional colloidal particles and nanochannels, soft colloidal particles and soft nanochannels can support excellent functions, respectively.…”
Section: Introductionmentioning
confidence: 99%